Complex program for the prevention of the development and progression of refractive errors in school year children - T.K. Botabekova; N.A. Aldasheva; V.R. Abdullina; I.S. Stepanova; B.I. Isergepova; Zh.S. Iskakbaeva (РМЖ "Клиническая офтальмология")
T.K. Botabekova1, N.A. Aldasheva2, V.R. Abdullina1, I.S. Stepanova1, B.I. Isergepova2, Zh.S. Iskakbaeva2 1Kazakhstan-Russian Medical University, Almaty, Kazakhstan 2Kazakhstan Research Institute of Eye Diseases, Almaty, Kazakhstan Aim: to develop a complex preventive and therapeutic program for refractive errors in school year children. Patients and Methods: 1,760 pupils of elementary, secondary, and high school of eight schools of Almaty (1,302 pupils of gymnasiums and 458 pupils of general education schools and sport boarding school) were examined. The 1st step was a preventive screening. The 2nd step was a distant interactive screening by teachers. The 3rd step was an eye examination of schoolers with low vision. The efficacy of the detection of visual impairments in schoolers during preventive and distant computer screening was compared. In addition, significant indicators for visual impairment monitoring in schoolers were identified. A "Program for the Prevention of the Development and Progression of Refractive Errors in Schoolchildren" was developed. To evaluate its efficacy, 140 pupils of general education schools with refractive errors and 1,302 pupils of gymnasiums with refractive er rors or their high risk underwent eye examinations. In addition, to compare the effect of wearing glasses/contact lenses with full correction on the quality of life, 31 schoolers aged 12–17 with refractive errors were selected. Results: the rate of visual impairments was 28.4% among the pupils of general education schools and 31.3% among the pupils of gymnasiums. The most common refractive error was myopia (46.9% and 65.4%, respectively). As children moved through their school carrier, the proportion of myopia tended to increase. Accommodative dysfunction ranked second 48.5% and 29.7%, respectively). Time spent on distant screening was twice less compared to time spent on preventive screening. Visual acuity, cycloplegic refraction, reserves of relative accommodation, and axial length (measured by ultrasound) were indicators of visual impairments in children during monitoring. Poor general health was reported in 33% of children who wear glasses and 15% of children who wear  contact lenses. Keywords: refractive errors, myopia, accommodation, schoolchildren, distant screening, prevention, vision correction with contact lenses. For citation: Botabekova T.K., Aldasheva N.A., Abdullina V.R. et al. Complex program for the prevention of the development and progression of refractive errors in school year children. Russian Journal of Clinical Ophthalmology. 2021;21(3):135–142 (in Russ.). DOI: 10.32364/2311-7729-2021-21-3-135-142.